Wawasan Jender Pemberdayaan Perempuan Pada Perspektif Ekonomi - Sumiharti, Sumiharti; Amral, Sainil (Jurnal Ilmiah Dikdaya, 2022)
The purpose of this study is to describe the gender insights of women's empowerment from an economic perspective in the novel Jendela-Jendela by Fira Basuki. This research uses structural studies, while the approach in this study is a qualitative approach and a descriptive method. The data in this study are words, sentences or expressions that lead to gender insights for women's empowerment from an economic perspective. The source of data in this study is the novel Jendela-Jendela by Fira Basuki. The results showed that there was a gender insight into women's empowerment that led to an economic perspective, namely the conflicts experienced by a female character named June. June is able to show that she is a female character who is able to actualize herself in a balanced way. With her empowerment, she was also able to balance the family's economic problems faced with the financial capabilities of her husband, Jigme. June's intelligence puts the economy in their home life under control and avoids gender-biased conflicts